0.5 V Current-Mode Low-Pass Filter Based on Voltage Second Generation Current Conveyor for Bio-Sensor Applications - Montree Kumngern; Fabian Khateb; Tomasz Kulej (My University, 2022)
This paper presents a low-voltage low-power current-mode third-order low-pass filter (LPF) based on voltage second generation current conveyor (VCII). The VCII utilizes the bulk-driven MOS transistor technique to achieve a wide input voltage range at low supply voltage of 0.5 V. Also, the VCII operates in the subthreshold region to achieve nano-power consumption of 390 nW. A third-order low-pass filter that is presented as an application of the VCII can operate as both current- and transimpedance-mode filters. The filter consumes 2.73 $\mu \text{W}$ and the total harmonic distortion (THD) is below 1 % for sine-wave input signal below 350 nA pp @ 10 Hz. The post-layout simulation results based on TSMC 0.18 $\mu \text{m}$ CMOS process are presented and confirms the futures of the filter.
Keywords: Current conveyor; Transimpedance amplifier; Analogue filter; Analog and Mixed-Signal Circuit Design